Functional Characterization of a Cassette-Speciﬁc Promoter in the Class 1 Integron-Associated qnrVC1 Gene - Fonseca, Érica Lourenço da (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Genética Molecular de Microrganismos. Rio de Janeiro, RJ, Brasil.